Diversity in the structure of Christian reasoning : interpretation, disagreement, and world Christianity - Broggi, Joshua D. (Studies in Systematic Theology, 2015)
Diversity in the Structure of Christian Reasoning examines the effect of Christian commitments on rationality. When Christians read scripture, traditions supply concepts that shape what counts as normal, good, and true. This book offers an account of how different communities produce divergent readings of the Bible. It considers two examples from World Christianity, first a Bakongo community in central Africa, and then a Tamil bishop in southern India. Each case displays a relation between tradition and reason that reconfigures the hermeneutical picture developed by Martin Heidegger and Hans-Georg Gadamer. To see what transpires when readers decide about a correct interpretation, this book offers theologians and scholars of religion a fresh strategy that keeps in view the global character of modern Christianity.